A Tax-Based Test of the Dividend Signaling Hypothesis - Bernheim, B. Douglas; Wantz, Adam (American Economic Review, 1992)
The authors propose and implement a new test of the dividend signaling hypothesis. Dividend signaling models generally imply that an increase in dividend taxation should increase the share price response per dollar of dividends (or 'bang-for-the-buck'). Many other dividend-preference theories have the opposite implication. An analysis of recent variations in tax policy reveals a strong positive relation between dividend tax rates and the bang-for-the-buck. Additional evidence on the relation between the bang-for-the-buck and other variables that are related to the marginal cost of paying dividends provides further support for dividend signaling. Copyright 1995 by American Economic Association.